Rhabdomyosarcoma of the biliary tract: a case report - Kouadir, Asmaa; Mazghi, Abderrahmane El; Hassouni, Khalid (International Journal of Contemporary Pediatrics, 2017)
Rhabdomyosarcoma (RMS) of the biliary tract is a rare tumor that commonly arises from the common bile duct. The most common clinical symptoms are obstructive jaundice and abdominal pain. Although diagnosis is often difficult and is frequently made during surgery, diagnostic imaging techniques including ultrasound, computerized tomography scan, and magnetic resonance cholangiopancreatography remain useful in the diagnosis and evaluation of biliary tree anatomy. In order to improve prognosis, different rhabdomyosarcoma study groups have adopted multidisciplinary treatment approach. Herein we describe a case of three-year-old child with Embryonal rhabdomyosarcoma originating in the common bile duct who was treated with surgery, chemotherapy according to European soft tissue sarcoma group (EpSSG) protocol and adjuvant postoperative intensity modulated radiotherapy to surgical bed with 6 MV photons to a dose of 41, 4Gy in 23 fractions. One year and a half after the end of therapy, the patient is still disease free. Although Rhabdomyosarcoma of the biliary tract is a rare tumor, it should be considered in the differential diagnosis of patients who have obstructive jaundice and a cystic mass within the common bile duct. Once believed to be an incurable disease, the prognosis of patients with biliary rhabdomyosarcoma has improved with a multidisciplinary treatment approach.